1995
DOI: 10.1215/03616878-20-1-31
|View full text |Cite
|
Sign up to set email alerts
|

Medigap Regulation: Lessons for Health Care Reform

Abstract: Congress enacted legislation in 1990 that dramatically changed the rules for selling supplemental health insurance, or "Medigap" policies, to the elderly. Most notably, policy coverage was standardized. Insurance carriers are allowed to sell only the ten specified packages of benefits, which reduces consumer choice but facilitates comparison shopping. This legislation is important in its own right and also offers lessons for U.S. health care reform. To examine the changes brought about by this legislation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 2 publications
0
13
0
Order By: Relevance
“…When the benefits to be included in the model Medigap plans were being debated by the National Association of Insurance Commissioners (NAIC), there was considerable concern over adverse risk selection if drug benefits were added. 4 In fact, the premiums for these plans tend to be much higher than those for other Medigap plans, and research has shown that insurance carriers are setting premium rates to account for the presence of adverse selection among plans with drug coverage. 5 Access to the remaining sources of coverage depends largely on a person's employment status and income, as well as geographic location.…”
mentioning
confidence: 99%
“…When the benefits to be included in the model Medigap plans were being debated by the National Association of Insurance Commissioners (NAIC), there was considerable concern over adverse risk selection if drug benefits were added. 4 In fact, the premiums for these plans tend to be much higher than those for other Medigap plans, and research has shown that insurance carriers are setting premium rates to account for the presence of adverse selection among plans with drug coverage. 5 Access to the remaining sources of coverage depends largely on a person's employment status and income, as well as geographic location.…”
mentioning
confidence: 99%
“…Unlike the Baucus Amendment, the OBRA-90 reforms were mandatory (Fox, Rice, and Alecxih 1995). OBRA-90 changed the industry in several significant ways.…”
Section: Legislative Initiativesmentioning
confidence: 99%
“…OBRA-90 also established consumer counseling programs, increased loss ratio requirements, prevented the sale of duplicate policies (by requiring a written statement from the consumer about existing policies), limited agents' commissions, and required a 6-month open-enrollment period (Rice and Thomas 1992;Short and Vistnes 1992;Fox, Rice, and Alecxih 1995).…”
Section: Legislative Initiativesmentioning
confidence: 99%
See 2 more Smart Citations